Etiological Spectrum and Outcome of Acute Kidney Injury in Children: A Tertiary Care Experience - Anjum, Muhammad Atif; Akhtar, Naureen; Perveen, Shahida; Chaudry, Adeela; Ain, Noor ul; Saud, Muhammad Sahir (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the aetiologies and outcomes which would help reduce preventable deaths from acute kidney injury.Study Design: Prospective longitudinal study.Place and Duration of Study: Paediatric Nephrology unit at University of Child Health Sciences, The Children’s Hospital Lahore Pakistan, from Aug 2021 to Jul 2022.Methodology: A total of 149 children who fulfilled the selection criteria were included in the study. Kidney Disease: Improving Global Outcomes guidelines were used for defining and staging acute kidney injury. The aetiology for each case of acute kidney injury was determined using standard workup/protocol and classified as pre-renal, renal and post-renal. Outcome parameters were recovery, improvement, death and progression to chronic kidney disease.Results: The mean age of children was 61.79±52.26 months, predominantly boys (68.5%). The most common etiological group was renal (73,49%), followed by pre-renal (53,35.6%) and post-renal (23,15.4%). It was observed that the majority of children had stage-3 AKI (63.8%), with kidney replacement therapy (KRT) given in 92(61.7%) cases. Mortality was seen in 30.9%, while recovery, improvement and death occurred in 69(46.3%), 44(29.5%) and 36(24.2%), respectively, at the time of discharge. At three months of follow-up, recovery, progression to chronic kidney disease, and death occurred in 73(49.0%), 20(13.4%) and 10(6.7%) children, respectively.Conclusion: Intrinsic renal disease was the most common etiological group occurring primarily in the form of AGN, and sepsis was found to be the most common underlying aetiology. Most patients presented in Stage 3 of acute kidney injury, and recovery was seen in many patients.